Physical virology: From virus self‐assembly to particle mechanics. (20th January 2020) - Buzón, Pedro; Maity, Sourav; Roos, Wouter H.
Abstract: Viruses are highly ordered supramolecular complexes that have evolved to propagate by hijacking the host cell's machinery. Although viruses are very diverse, spreading through cells of all kingdoms of life, they share common functions and properties. Next to the general interest in virology, fundamental viral mechanisms are of growing importance in other disciplines such as biomedicine and (bio)nanotechnology. However, in order to optimally make use of viruses and virus‐like particles, for instance as vehicle for targeted drug delivery or as building blocks in electronics, it is essential to understand their basic chemical and physical properties and characteristics. In this context, the number of studies addressing the mechanisms governing viral properties and processes has recently grown drastically. This review summarizes a specific part of these scientific achievements, particularly addressing physical virology approaches aimed to understand the self‐assembly of viruses and the mechanical properties of viral particles. Using a physicochemical perspective, we have focused on fundamental studies providing an overview of the molecular basis governing these key aspects of viral systems. This article is categorized under: Biology‐Inspired Nanomaterials > Protein and Virus‐Based Structures Nanotechnology Approaches to Biology > Nanoscale Systems in Biology Abstract : Viruses are highly ordered supramolecular complexes that have evolved to propagate between related organisms. Although viruses are very diverse, they share common functions and properties. In this review, we aim to provide an overview of virus self‐assembly and viral particle mechanics, summarizing the latest scientific achievements within these areas.